Politik Hukum di Bidang Ekonomi dan Pelembagaan Konsepsi Welfare State di dalam Undang-Undang Dasar 1945 - Prasetyo, Kukuh Fadli (Jurnal Konstitusi, 2012)
Welfare state conception has been adopted in the substance of the 1945 Constitution of Republic Indonesia (UUD 1945), that extracted in fourth paragraph of Preambule of UUD  1945,  by  posting  the  phrase  ‘to  improve  public  welfare’  as staatsidee of Republic of Indonesia. In amendment of UUD 1945, UUD 1945 determines economic democracy principles, as prescribed in Article 33 paragraph (4) UUD 1945. In its economic democracy, there is efficiency with justice principle that recognized as capitalistic unsure which lifts the spirit of neoliberalism. After analysing that corelation, I found and identify that some unsures of neoliberalism has been emulted in some legal policy in economic issued by the Administration of Indonesia, such as privatisation, market regulation, deregulation, and reducing public spending.